Andexanet to reverse apixaban or rivaroxaban anticoagulation. Issue 9 (22nd October 2019) - Chaplin, Steve
Abstract : Andexanet alfa (Ondexxya) is the first licensed antidote to the direct factor Xa inhibitors apixaban or rivaroxaban, for use when reversal of anticoagulation is needed due to life‐threatening or uncontrolled bleeding. This article summarises its indications, efficacy and safety.